TOXOPLASMA SEROPOSITIVITY IN A STATE HOSPITAL FOR A YEAR - Beytur, Leyla; Iraz, Meryem; Karadan, Mesut; Karci, Erdal; Firat, Pinar Yuce; Turan, Ayse; Karaman, Ulku (Marmara Univ, Fac Medicine, 2010)
Objective: Toxoplasma gondii is an obligate intracellular protozoan parasite, which causes a common infection called toxoplasmosis. Toxoplasmosis is generally an asymptomatic infection and, if it develops during pregnancy, it can cause abortus, still birth, preterm birth, or congenital anomalies. The purpose of the study was to find the prevalence of the Toxoplasma IgG, and IgM among patients admitted to our hospital between 2008-2009. Methods: In the study 205 subjects were examined for IgM and IgG and 27 subjects were examined only for IgM. The subjects were 40,48 +/- 20,14 years of age. The data were analyzed using the Pearson Chi-Square, Yates's corrected Chi-square and Fisher's Exact Chi-Square tests. Results: The analyses revealed a IgM positivity rate of 0.9 % and IgG seropositivity rate of 30.7% and no significant correlation was found between gender and age. Conclusion: It was concluded that, the level of parasite seropositivity in the region was significantly high, indicating that particularly pregnant women or women planning a possible pregnancy should receive regular medical examination for parasite positivity.
Keywords: Toxoplasma gondii; IgG; IgM Seropositivity